Steric and electronic effect in unsymmetrical squaraine dyes for dye-sensitized solar cells - Nawghare, Indrajeet S.; Singh, Ambarish Kumar; Maibam, Ashakiran; Krishnamurty, Sailaja; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Journal of physical chemistry C, 2023)
Functionalizing the light harvesting sensitizers with additional electron-donating or -withdrawing groups is a potential approach to modulate the photophysical and electrochemical properties which in-turn optimizes the driving force associated with the charge injection and dye-regeneration processes at the dye-TiO2/electrolyte interface and the photovoltaic device performance in dye-sensitized solar cells (DSSCs). Furthermore, modulated electronic levels of the dyes provide an opportunity to reduce the overpotential associated with the dye-regeneration process and make the dye-TiO2 interface compatible with various electrolytes. Furthermore, an in-built steric feature by means of introducing linear/branched alkyl groups in the sensitizer is important in controlling the aggregation of dyes on the TiO2 surface. Hence, to integrate both steric and electronic properties, a series of alkyl group-wrapped unsymmetrical squaraine dyes (SQ-X) with electron-donating and -withdrawing groups have been designed, synthesized, and utilized for DSSC device fabrication. These dyes are functionalized with alkyl groups at both sp(3)-C and N-atoms of the indoline donor moiety at the nonanchoring side to have a similar steric feature. Photophysical and electrochemical studies revealed that the HOMO and LUMO energy levels of the SQ-X series of dyes have been modulated systematically with sufficient driving forces for both charge injection and dye-regeneration processes with iodolyte (I-/I-3(-)) electrolyte. In the presence of electron-donating groups in SQ-X (where X = -NPh2 and -OMe), the HOMO energy levels are less positive than SQ-H, whereas the presence of electron-withdrawing groups such as -CO2Me, -CN, and -NO2 pushed the HOMO energy levels toward more positive potentials. Enhanced photovoltaic performances have been obtained for the dyes containing electron-donating groups, where the dye with the -NPh2 group showed a maximum of eta 7.03% (V-OC 708 mV, J(SC) 13.16 mA cm(-2), and ff 78%). The dye with the strong electron-withdrawing group -NO2 showed an efficiency of 1.49% (V-OC = 634 mV, J(SC) = 3.13 mA cm(-2), and ff 75%). As the dyes with the electron-withdrawing group possess deep positive HOMO energy levels, the DSSC device characterization has been investigated with the Cu+/2+ redox shuttle. The reduced device performance of electron-withdrawing-group-containing dyes is due to the unfavored charge distribution in the LUMO compared to the presence of electron-donating-group-containing dyes, and it was supported by the difference in the charge injection efficiency.
Keywords: cobalt; Donor; Dynamics; Organic dyes

Squaraine dyes as efficient photoredox catalysts for PET-RAFT polymerization in batch and flow modes accelerated by suppression of dye aggregation - Patil, Anil M.; Nawghare, Indrajeet S.; Nithyanandhan, Jayaraj; Ambade, Ashootosh V. (Macromolecules, 2025)
Organic photoredox catalysts (PCs) based on squaraine dyes are investigated for photoinduced electron transfer-reversible addition-fragmentation chain transfer (PET-RAFT) polymerization under visible-light (lambda max = 485 nm) irradiation in the presence of triethylamine that suppresses self-aggregation of dye and accelerates the polymerization. Several commonly used PCs are also screened, and self-aggregation is found to be reduced with triethylamine, thus providing a simple and effective approach to reduce aggregation of PCs. There is no induction period, and total polymerization time is shorter for squaraine dye PCs than for reported PCs under similar conditions. The photocatalyst system is amenable to polymerization by using different RAFT agents. Methyl methacrylate and a range of functional methacrylates are polymerized with good control over molecular weight and narrow dispersity in a first-order reaction with a random switch ``ON-OFF'' of the light source and even without an inert atmosphere. The mechanism of polymerization without and with requirement of triethylamine is elucidated using control experiments and found to be an oxidative and reductive electron transfer, respectively. A series of diblock and random copolymers of methyl methacrylate with methacrylate monomers are synthesized. Controlled polymerization is also demonstrated using a continuous-flow method and in an aqueous medium.